A parallel time-domain wave simulator based on rectangular decomposition for distributed memory architectures. (October 2015) - Morales, Nicolas; Mehra, Ravish; Manocha, Dinesh
Abstract: We present a parallel time-domain simulator to solve the acoustic wave equation for large acoustic spaces on a distributed memory architecture. Our formulation is based on the adaptive rectangular decomposition (ARD) algorithm, which performs acoustic wave propagation in three dimensions for homogeneous media. We propose an efficient parallelization of the different stages of the ARD pipeline; using a novel load balancing scheme and overlapping communication with computation, we achieve scalable performance on distributed memory architectures. Our solver can handle the full frequency range of human hearing (20 Hz–20 kHz) and scenes with volumes of thousands of cubic meters. We highlight the performance of our parallel simulator on a CPU cluster with up to a thousand cores and terabytes of memory. To the best of our knowledge, this is the fastest time-domain simulator for acoustic wave propagation in large, complex 3D scenes such as outdoor or architectural environments.